Jim Harrison : complete poems - Harrison, Jim, 1937-2016 (Copper Canyon Press, 2021)
"This tour de force contains every poem Harrison published over his fifty-year career, as well as a section of unpublished "Last Poems." Here are the nature-based lyrics of his early work, the high-velocity ghazals, a harrowing prose-poem "correspondence" with a Russian suicide, the riverine suites, fearless meditations inspired by the Zen monk Crazy Cloud, and a buoyant conversation in haiku-like gems with friend and fellow poet Ted Kooser"--